Investigation of the pathways involved in the acquired radioresistant EMT6 mouse mammary carcinoma cells to gamma-ray irradiation: in vitro and in vivo studies / Nur Fatihah Ronny Sham - Ronny Sham, Nur Fatihah (2024)
Resistance of breast cancer to radiotherapy is the crucial aspect leading to relapse and low survival rate. Radioresistance is suggested to be linked with epithelial-mesenchymal transition (EMT), a process involved in regulating cancer tissue remodelling, resulting in recurrence and metastasis. The underlying mechanisms in acquiring radioresistance to gamma-ray in mouse mammary cancer cell lines (EMT6) were investigated using both in vitro and in vivo approaches. EMT6 cells were irradiated with gamma-ray at 2 Gy/cycle to initiate the development of radioresistance in vitro. Confirmation of EMT6 cells acquired radioresistance was analysed using migration and clonogenic assays. Next-generation sequencing analysis validated 16 genes of interest (GOI) via real-time polymerase chain reaction (qPCR). The signalling pathways and proteins involved in EMT6 cells acquiring radioresistance were verified by KEGG pathway analysis and western blotting, respectively. EMT6RR_MJI radioresistance cells were developed from parental EMT6 cells after 8 cycles of fractionated gamma-ray irradiation. This is confirmed by irradiation with gamma-ray at 2, 4, and 8 Gy, which resulted in higher survival fractions and migratory rates of EMT6RR_MJI compared to parental cells.